Fall armyworm (Spodoptera frugiperda) in Africa: insights into biology, ecology and impact on staple crops, food systems and management approaches - Togola, Abou; Beyene, Yoseph; Bocco, Roland; Tepa-Yotto, Ghislain; Gowda, Manje; Too, Abel; Boddupalli, Prasanna (Frontiers in Agronomy, 2025)
The fall armyworm (FAW), Spodoptera frugiperda, is a polyphagous pest native to the American continent that was first detected in Africa in 2016, where it has since become a major constraint to agriculture. This species severely damages staple crops like maize, sorghum, and rice, threatening food security and the livelihoods of millions of smallholder farmers. Maize, the most vulnerable crop in sub-Saharan Africa, suffers significant annual losses due to the destructive impact of FAW, which affects agricultural productivity and overall rural economies. The pest displays complex biological and ecological patterns that are highly dependent on environmental factors, host plant availability, and natural enemy diversity, making control efforts challenging. This review explores the traits driving FAW’s invasive success in Africa, summarizing key findings on its biology and ecology while outlining current management strategies. It underscores the importance of Integrated Pest Management (IPM), which includes cultural practices, biological control, mechanical/physical methods, host plant resistance, and judicious application of chemicals. Regular crop monitoring and surveillance principles are also discussed as prevention and early detection measures to mitigate FAW damage. Future directions emphasize the need for collaboration among stakeholders, including international research organizations, to effectively control FAW invasion. Given the economic risks of the FAW outbreak in Africa, adopting IPM solutions is crucial for reducing pesticide reliance and ensuring stable agricultural production. This review offers valuable insights into achieving this goal.